The correlation between melatonin and sleep quality in pediatric patients with atopic dermatitis—A systematic review. - Pinto Ferreira, I.; Mendes Ribeiro, J.; José Reinaldi Serra, M.; Esteves Vagnozzi Rullo, V. (European Journal of Pediatric Dermatology, 2024)
Objectives. The aim of this study is to investigate the difference between serum melatonin levels in patients with and without severe atopic dermatitis (AD) and to evaluate the effects of melatonin administration on sleep and quality of life in these children. This study presents new aspects in the field of medical knowledge by demonstrating the improvement of the atopic dermatitis score (SCORAD) index in AD patients who received oral melatonin, as well as the improvement of sleep quality. This information suggests the possibility of improving the patient’s quality of life, as the symptoms of this chronic and recurrent condition can be reduced by improved nighttime sleep. Methods. Three databases were used and, after applying the inclusion and exclusion criteria, five studies were selected, including three case-control studies and two randomized clinical trials (RCTs). The methodological quality of randomized trials was assessed using the Cochrane Risk of bias Tool for Randomized Trials, while that of case-control studies was assessed using the Newcastle-Ottawa scale. Results. One case-control study found that AD patients had significantly lower serum melatonin levels, while two other case-control studies found higher serum levels in AD patients compared to the control group. In RCTs, a decrease in atopic dermatitis score (SCORAD index) and sleep-onset latency was found in those taking melatonin supplements, while an increase in total sleep time was observed. Conclusions. It is not possible to confirm a difference in serum melatonin levels in pediatric patients with AD compared to the non-AD population. The use of oral melatonin appears to be a promising alternative in the treatment of insomnia in patients with AD.